The effect of energy construction adjustment on the dynamical evolution of energy-saving and emission-reduction system in China. (15th June 2017) - Fang, Guochang; Tian, Lixin; Fu, Min; Sun, Mei; Du, Ruijin; Lu, Longxi; He, Yu
Highlights: Use nonlinear method to model the ESER system with multiple variable constraints. Energy construction adjustment could effectively control energy intensity. ESER system will crash with improper economic input or energy construction adjustment. Economic input is the key variable affecting energy construction adjustment and ESER. Abstract: This paper attempts to explore the effect of energy construction adjustment on the energy-saving and emission-reduction (ESER) dynamical evolution system. Based on the nonlinear dynamics theory, the dynamic behavior of the novel system is discussed. The quantitative coefficients of the actual system are identified with the aid of genetic algorithm-back propagation neural network. Scenario analysis results show that, energy construction adjustment could effectively control energy intensity. To clarify this further, an example of 4D ESER system with new energy constraints is demonstrated. Investigation results show that, government control can effectively control energy intensity, while brings inhibiting impact on economic growth and people's livelihood. Economic investment is the key variable affecting energy construction adjustment and ESER, the ESER system will crash when the investment is too low. Energy construction adjustment could effectively reduce energy intensity. However, the ESER system will also crash if the development of energy construction adjustment is too fast. The interesting thing is that the ESER system should be pulled back to steady state as the investment getting bigger. Energy intensity could be controlled in expected range by taking adequate measures. Full use of the role of energy structure adjustment should be made to promote the development of new energy, while government control is used only when necessary.